COMPRESSED DOMAIN DATA HIDING APPROACH ON ENCRYPTED IMAGES USING AUXILIARYINFORMATION - Amruta Nehete; Deepak Pawar (International Journal of Innovations in Engineering Research and Technology, 2021)
This paperpresents secretdata concealment and compressing encrypted images based on auxiliary information generation for efficient secure transmission under insufficient bandwidth. The process starts by encryption ofuncompressed original images and generation of someauxiliary information, which will be used for data compression and image reconstruction. Then, the channel provider compress the encrypted data by a quantization method with optimal parameters that are derived from a part of auxiliary information and transmit the compressed data, which includesan encrypted sub-image, the quantized data, the quantization parameters and another part of auxiliary information. In this projectdiscrete cosine transform is used under the quantization method for encrypted image compression. The secret text messageis first converted to bit streams then it will be concealed into encoded bits of generated binary map.